Contending perspectives in economics : a guide to contemporary schools of thought - Harvey, John T. (Cheltenham Edward Elgar Publishing Ltd., 2015)
​'This wise and lucid guide to pluralism in economics embodies the values of its cause. Generous, open-minded, fair, accurate and accessible: John Harvey's new book is a fine achievement that every economics major should read.' - James K. Galbraith, The University of Texas at Austin, US John Harvey's accessible book provides a non-technical yet rigorous introduction to various schools of thought in economics. Premised on the idea that economic thinking has been stunted by the almost complete rejection of anything outside the mainstream, the author hopes that this volume will open readers' minds and lead them in new and productive directions". (from Amazon page)
1Introduction -- 2. Economics as a Scientific Discipline -- 3. Neoclassical Economics -- 4. Marxism -- 5. Austrian Economics -- 6. Post Keynesian Economics -- 7. Institutionalism -- 8. New Institutionalism -- 9. Feminist Economics -- 10. Conclusions
Includes bibliographical references and Index.
Keywords: Economics; ECONOMIC THOUGHT; COMPARATIVE ECONOMICS